Kinetics of Boron Adsorption in Soils of Assam State, India - Tamuli, Babita; Bhattacharyya, D.; Borua, N.G.; Basumatary, A.; Das, K.N.; Kurmi, K. (Asian Journal of Chemistry, 2016)
Batch studies were conducted to investigate the adsorption behaviour of boron in four major soil orders of Assam viz. entisol, inceptisol, alfisol and ultisol, which had wide variations in physico-chemical properties. Three mathematical models (viz., zero order, first order and parabolic diffusion) were used to describe kinetics of boron adsorption. The boron adsorption pattern was characterized by an initial fast reaction followed by a slow process and the equilibrium was attained in 24 h of equilibration. The boron adsorption with respect to reaction time was positively and significantly correlated with organic carbon content (r = 0.901**), clay (r = 0.964**), free Fe2O3 (r = 0.774**), free Al2O3 (r = 0.868**) and total free Fe2O3 + Al2O3 (r = 0.882**) of the soils. The parabolic diffusion equation was found to be the best to describe the rate of boron adsorption as indicated by the highest values of coefficient of determination, R2 (0.980 to 0.985) and lowest values of standard error (SE) (6.56 to 10.76) over the entire time range from 0 to 70 h. This observation leads to the conclusion that the adsorption of boron in soils of Assam was mainly controlled by diffusion.